2007
DOI: 10.1186/1476-4598-6-75
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of cancer stem cell in human lung adenocarcinoma A549 cells

Abstract: Background: The studies on cancer-stem-cells (CSCs) have attracted so much attention in recent years as possible therapeutic implications. This study was carried out to investigate the gene expression profile of CSCs in human lung adenocarcinoma A549 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 39 publications
3
62
0
Order By: Relevance
“…Furthermore, CD338 can promote resistance to multiple drugs and has been observed in many types of TICs (Bertolini et al, 2009). Lung cancer stem cells, isolated with Hoechst 33342, were found to express significantly higher levels of CD338 (Seo et al, 2007). In our study, we found that the TICs we isolated strongly had highly expressed CD133 + /CD338 + , possessed proliferation and enhanced tumorigenesis capacities, and more highly expressed of stem cell-associated genes.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, CD338 can promote resistance to multiple drugs and has been observed in many types of TICs (Bertolini et al, 2009). Lung cancer stem cells, isolated with Hoechst 33342, were found to express significantly higher levels of CD338 (Seo et al, 2007). In our study, we found that the TICs we isolated strongly had highly expressed CD133 + /CD338 + , possessed proliferation and enhanced tumorigenesis capacities, and more highly expressed of stem cell-associated genes.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, Wang et al showed that knockdown of IL-6R diminished stemness and survival of glioma stem cells (26). In our previous studies, we have isolated lung CSCs using the Hoechst 33342 exclusion assay and demonstrated that IL-6R expression is upregulated in CSCs (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, any markers useful for detection of CSCs in lung cancer have not been known. Recently, Seo et al 22 reported that several genes were highly expressed in SP of lung adenocarcinoma cell lines: one of them was the gene for NR0B1, a recently characterized member of the orphan nuclear receptor family. 23 NR0B1 (also called dosage-sensitive sex reversal/adrenal hypoplasia congenital critical region on the X chromosome 1; DAX1) acts as a negative regulator of steroid production, and is expressed in the reproductive and endocrine systems.…”
mentioning
confidence: 99%